Children educare center system - Mahmud, Murni; Abdul Karim, Muhammad Firdaus (IIUM Press, 2011)
Educational website is website that provides education info either for student or others people. Most of educational websites in Malaysia just provide infonnation about institute itself as a platfonn to promote their institute. They do not provide other features such as online registration, profile infonnation, download and so on. Other than that, there are not many educational websites that implemented Islamic elements in them. Therefore, this chapter presents a new interactive educational website called Children Educare Center System, by implementing Islamic environment like the following existing websites; Genius Aulad, Tadika Atfal and Tadika Bijak. It is hoped that this chapter can assist readers in viewing educational website as a more useful platfonn rather than just giving infonnation, Insha Allah